Travels in Koordistan, Mesopotamia etc. : including an account of parts of those countries Hitherto unvisited by Europeans with sketches of the character and manners of the Koordish and Arab tribes. - Fraser, James Baillie, 1783-1856 ([Boston])
2 c. (viii, 382 s. ; ix, 477 s.)